Theory of planned behaviour to predict responsible ecotourism: structural equation modelling - Ibrahim, Hayati; Mariapan, Manohar; Lim, Evelyn Ai Lin; Bidin, Sheena (Human Resource Management Academic Research Society, 2022)
In sustainable ecotourism, responsible ecotourist behaviour towards purchasing local products and services is vital to alleviate poverty in local communities and help wildlife conservation. This study was conducted to test the relationship between attitude, anticipated emotion, and environmental concern to predict responsible ecotourist behavioural intention to purchase local products and services for wildlife conservation in Penang National Park. Study samples were obtained using the purposive sampling method, and questionnaires were distributed face to face in Penang National Park. Statistical Software Packages, namely SPSS Amos version 26.0, were used to perform data analysis to run Structural Equation Modelling (SEM). Out of the nine hypotheses that have been proposed, 8 of them are supported. The findings of the study found that attitude has a significant relationship with intention, anticipated emotion has a significant relationship to attitude, environmental concern has a significant effect on attitude and anticipated emotion, and environmental concern has no significant effect on intention. Mediation analysis found that attitude is a mediator between anticipated emotion and intention, and attitude is also a mediator between environmental concern and intention. Mediation analysis also found that anticipated emotion is a mediator between the relationship of environmental concern and intention. This study is critical in assisting stakeholders in the ecotourism industry in planning an effective marketing strategy to promote local products and services.